2010
DOI: 10.1186/1476-4598-9-13
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of cholangiocarcinoma-derived fibroblast reveals alterations related to tumor progression and indicates periostin as a poor prognostic marker

Abstract: BackgroundFibroblasts play important roles in several cancers. It was hypothesized that cholangiocarcinoma (CCA)-associated fibroblasts (Cfs) differ from non-tumorigenic liver fibroblasts (Lfs) in their gene expression profiles resulting in the capability to promote cancer. Periostin (PN) is a multi-functional protein and has emerged as a promising marker for tumor progression. The role of PN in CCA, however, has not yet been explored.ResultsIn this study, the gene expression profile of Cfs in comparison to Lf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
147
3
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 125 publications
(167 citation statements)
references
References 58 publications
15
147
3
2
Order By: Relevance
“…Postn immunoreactivity, which has been observed to colocalize with α‐SMA immunostaining in human6 and in rat BDEneu ICCs,1 was seen by us to be most extensive in the stroma of the more aggressive BDEneu liver cholangiocarcinomas of increasing tumor mass and anaplasia over that observed in the slow growing well‐differentiated BDEsp tumors and intermediate growing well‐to‐moderately differentiated TDE CC tumors. That Postn protein was also determined by both immunohistochemistry and western blotting to be more prominent in the larger sized BDEneu liver tumors than in the smaller BDEneu liver tumors also appears to reflect an increased accumulation of α‐SMA + CAFs within the enlarging desmoplastic stroma of the larger sized liver tumors 1.…”
Section: Discussionsupporting
confidence: 50%
See 4 more Smart Citations
“…Postn immunoreactivity, which has been observed to colocalize with α‐SMA immunostaining in human6 and in rat BDEneu ICCs,1 was seen by us to be most extensive in the stroma of the more aggressive BDEneu liver cholangiocarcinomas of increasing tumor mass and anaplasia over that observed in the slow growing well‐differentiated BDEsp tumors and intermediate growing well‐to‐moderately differentiated TDE CC tumors. That Postn protein was also determined by both immunohistochemistry and western blotting to be more prominent in the larger sized BDEneu liver tumors than in the smaller BDEneu liver tumors also appears to reflect an increased accumulation of α‐SMA + CAFs within the enlarging desmoplastic stroma of the larger sized liver tumors 1.…”
Section: Discussionsupporting
confidence: 50%
“…Its potential as an independent prognostic risk factor for poor survival for patients with ICC was first suggested by Utispan et al,6 who demonstrated that surgically resected ICC patients with tumors strongly immunostained for CAF‐Postn had significantly shorter postoperative survival times than those expressing low levels of Postn. Benign liver diseases (e.g., liver cirrhosis, focal nodular hyperplasia) were further reported to show no‐to‐slight Postn immunoreactivity, and Postn expression was not detected in the cancer cells of conventional hepatocellular carcinoma (HCC) 6, 10. Patients with cholangiocarcinoma were also reported to exhibit a significantly higher median Postn level in their serum than those with normal liver, liver cirrhosis, HCC, or other malignancies 10.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations